Crises of Legitimacy? Warfare, National Identity, and Counterinsurgency Tactics in the Public Imagination - Höpker, Karin (New American Studies Journal: A Forum, 2022)
For our special issue of the New American Studies Journal “American Crises” I had the opportunity to speak with Dr. Barbara Elias, Associate Professor at the department of Government and Legal Studies at Bowdoin College, Maine, who specializes in international relations, U.S. foreign policy, national security, and political Islam.<br